Hubungan Religiusitas dengan Citra Tubuh pada Wanita Dewasa Awal - Dessy Sumanty; Deden Sudirman; Diah Puspasari (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2018)
This research attempts to relate the body image phenomenon with the level of subject religiosity. This research used correlational research design that was involving 332 respondents. The statistical testing which is used to test the hypothesis Rank Spearman. The calculation result with the significance level of trust 95% (a = 0.05) show that the correlation coefficient is 0.083 and p-value is 0.129. It means that Ho is accepted and H1 is rejected. It can be concluded that there is no relationship between religiosity with body image.